(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
To ensure poetic individuality in the language of a work of art, the creators try to make maximum use of linguistic units. In particular, synonyms, antonyms, phraseological units, vulgar, barbaric words are the main means in the full disclosure of creative intent. In this article, the skill of the poet Tashpolat Ahmad in using words, the Creator’s ability to skillfully use linguistic units are revealed by illustrative examples. Each theoretical idea is proved by examples taken from the poet’s poems.